Adult Intestinal Malrotation Treated with Laparoscopic Ladd Procedure - Noritoshi Mizuta; Takuya Kikuchi; Yoshiyuki Fukuda (Case Reports in Surgery)
Intestinal malrotation is a rare congenital disease caused by abnormal intestinal rotation and fixation of the intestinal tract in the early embryonic state. Adult cases are rare. A laparoscopic Ladd procedure for adult intestinal malrotation is increasingly reported, but owing to the rarity, some important aspects of the disease and its treatment may be overlooked. Three adult cases of intestinal malrotation that underwent surgery at our hospital between January 2019 and October 2020 were retrospectively examined about patient backgrounds, short-term results, and complications. All patients were male, median age was 54.6 years, and the complaints were abdominal pain and/or distention. No midgut volvulus was observed. The laparoscopic Ladd procedure was performed for all cases. One patient underwent reoperation (duodenoduodenostomy) because of impaired passage of the duodenal descending section due to postoperative pancreatic fistula. The postoperative courses of the other two patients were good. No recurrence of symptoms was observed in any of the cases. The reason for reoperation in one of the cases is considered to be pancreatic injury when the severe curve from the duodenum to the upper jejunum near the pancreatic head was straightened. Correction of the curve is important to improve passage disorder of the duodenum, but special care is required to avoid organ damage, especially during a laparoscopic procedure with forceps. The laparoscopic Ladd procedure for adult intestinal malrotation is recommended if there is no midgut volvulus; it is minimally invasive and a comparatively simple technique, but surgeons should take special care to avoid organ damage.